Multiple pregnancy. Case report. - Práxedes Regla Rojas Quintana (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
We present a case of a 34-year-old white female patient, of rural origins, with a history of 3rd degree bronchial asthma and respiratory arrests for that cause, who has required several admissions in the ICU. Gestation history 1, no deliveries, 1 abortion and secondary infertility, for which she was treated, along with her spouse, in the infertility consultation, in which ovulation disorders were diagnosed, consisting of bilateral tubaric obstruction on her and severe oligospermia on her spouse, for which they underwent combined surgical treatment. Tubaric permeability with hydrotubation was first accomplished, then ovulation and spermatogenesis with clomiphene citrate and then low-technology fertilization was performed, resulting in a quadruple pregnancy, which satisfactorily arrived to full term at 34 weeks of gestation. Due to the mother's medical history, the risks involved in this type of pregnancy and its happy outcome, we decided to publish the case.